PENGARUH JUMLAH TENAGA KERJA DAN TOTAL ASET TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH DI KECAMATAN LANGSA KOTA - Shelly Midesia (J-ISCAN: Journal of Islamic Accounting Research, 2022)
This study aims to test the effect of the number of workers and total assets on the employment of MSMEs in Langsa Kota District in 2017. The total population of MSMEs in Langsa Kota District is 1,669 MSMEs, taking the number of MSMEs as a sample using the slovin formula of 323 MSMEs and selecting samples using random sampling. The data used in this study is cross-sectional data, namely data in the form of the number of workers, total assets and income of MSMEs in 2017. The data analysis method used is multiple linear regression. The results showed that the number of workers had a negative and significant effect on the income of MSMEs with a coefficient value of -0.036 and a sig value. 0.001. Total assets have a positive and significant effect on MSME income with a coefficient value of 0.953 and a sig value. 0.001. The number of workers and total assets have a significant effect on the income of MSMEs in Langsa Kota District and the value of adjusted R2 is 98.6%.